Relationship of Triglyceride Levels with the Incidence of Acute Coronary Syndrome in Patients with Type 2 Diabetes Mellitus at RSPAL Dr. Ramelan Surabaya - Tan Wulan Pakungwati; Hendrata Erry Andisari; Amiril Mu’minin (International Journal Labs, 2026)
Type 2 Diabetes Mellitus (DM) is a major global health issue with increasing prevalence, including in Indonesia, where it significantly contributes to cardiovascular diseases such as Acute Coronary Syndrome (ACS). This study investigates the relationship between triglyceride levels and ACS occurrence in Type 2 DM patients at RSPAL Dr. Ramelan Surabaya. The objective is to explore triglyceride distribution, examine its relationship with ACS, and assess age and gender variations in ACS incidence. Using a cross-sectional observational design, secondary data from the medical records of 92 patients were analyzed. The study found that a high percentage of patients had lipid metabolism disorders, with most exhibiting normal triglyceride levels. The distribution of ACS events revealed that APTS was most prevalent, followed by IMA-EST. Spearman correlation tests showed no statistically significant relationship between triglyceride levels and ACS occurrence (p > 0.05). However, the study indicated that other multifactorial risk factors, such as age, gender, and lifestyle factors, played a more crucial role in the incidence of ACS in Type 2 DM patients. This study suggests that while triglyceride levels alone may not serve as a significant predictor, they could be useful in conjunction with other risk factors for early detection and prevention strategies in clinical settings. Further research is needed to explore causality and develop more effective treatment protocols.